Social-ecological filters influence plant and invertebrate diversity in educational gardens in a South American metropolis - Herrera-Oesterheld, Maria Sofia; Paecke, Sonia Reyes; Munoz, Alejandra E.; Amouroux, Paul; Trujillo, Catalina; Ibarra, Jose Tomas (My University, 2025)
Educational gardens are green areas in schools that are cultivated with vegetables and are at least partially under the care of students. Although they are usually small in size, they can be biodiversity refuges and act as stepping stones for the flow of species within cities. Biodiversity in educational gardens may be "filtered" by social-ecological processes occurring within the garden, around the garden, and by management practices. This study analyzed species richness and the social-ecological filters that may influence plants and invertebrates in school gardens in the Metropolitan Area of Santiago (MAS), Chile. We sampled 33 vegetable gardens in municipal schools, identifying vascular plants (cultivated and spontaneously growing) and invertebrate morphospecies richness in gardens. We further measured the area of the garden, classified the garden's ground cover and the land cover around the garden's buffer zone, and conducted an interview with the main gardener. A total of 362 plant species and 127 invertebrate morphospecies were recorded. The most influential social-ecological filters of plant richness were garden area (m2), percentage of cultivated ground cover, and irrigation during the summer. The most influential factors influencing invertebrate richness were plant species richness, bare ground cover (with a negative effect) and, to a lesser extent, tree cover in the garden's buffer zone and irrigation during the summer. We conclude that the biodiversity of school gardens in the MAS is more related to social-ecological filters within the garden and management practices than to filters within the garden's buffer zone.
Keywords: chile; garden management practices; school gardens; sustainability education; urban agriculture; urban biodiversity